Pengaruh Program E-SAMSAT, SAMSAT Keliling, dan Kepuasan Wajib Pajak pada Kepatuhan Wajib Pajak Kendaraan Bermotor - Megayani, Ni Komang Megi; Noviari, Naniek (E-Jurnal Akuntansi; Vol 31 No 8 (2021)DO - 10.24843/EJA.2021.v31.i08.p05, 2021)
The research aims determine the effect of e-SAMSAT, SAMSAT roving, and taxpayer satisfaction on motor vehicle taxpayer compliance. The theories used in this study are Theory of Planned Behavior and the Technology Acceptance Model theory. This research was conducted at the Joint Office of SAMSAT Karangasem with a total population of 205,849 taxpayers and sample size was calcula . ted using the Sl . ovin form . ula so that the sample size was 100 taxpayers. The method of determining the sample using accidental sampling is taking samples by chance. Data collect . ion was carr . ied out by distributing questio . nnaire, and the analy . sis technique used was multi . ple linear regress . ion analysis. Based on resul . ts of the analy . sis, it is concluded that the e-SAMSAT program, SAMSAT roving, and taxpayer satisfaction have a positive effect on motor vehicle taxpayers compliance at the Joint Office of SAMSAT Karangasem. Keywords: E-SAMSAT Program; SAMSAT Roving; Tax Payer’s Satisfaction; Taxpayer Compliance.